Textual Metafunction in Taylor Swift's Graduation Speech 2022 - Ayunani, Meliana Aulia; Sugaryamah, Deuis; Suswanto, Deni (Edukasi Lingua Sastra, 2025)
Graduation speech is one of the particular speeches that graduates or teachers in the graduating field are required to give (Assidiqi & Cahyono, 2023). In this case, Taylor Swift is trusted to give the commencement speech because she is the recipient of the Honorary Doctorate of Fine Arts degree awarded by NYU (New York University) in appreciation of her outstanding achievements in the music industry and her lasting influence on popular culture. Therefore, this study aims to analyze textual metafunction realization in the speech, also examining the thematic progression that make clauses coherent and cohesive. This research employes descriptive qualitative method within Systemic Functional Linguistics framework. From the analysis that has been done, 341 clauses were found in Taylor Swift's Graduation Speech 2022. The most dominant theme type is topical theme, which is found in every clause in the speech. Following by textual theme, which is found in 115 clauses. The least theme type found is interpersonal theme, which is only found in 15 clauses. This research also found the use of Thematic progression pattern in Taylor Swift's graduation speech. Three main patterns of thematic progression namely constant theme pattern, linear/zig-zag pattern, multiple rheme pattern are used in the speech.